Konsentrasi hambat minimum dan konsentrasi bunuh minimum ekstrak etanol dan nanopartikel ekstrak etanol daun matoa (Pometia pinnata) terhadap Cutibacterium acnes - Safira , Liyuza; Rahayu, Yayuk Putri; Nasution , Haris Munandar; Miswanda, Dikki (Journal of Pharmaceutical and Sciences, 2025)
Infectious diseases are caused by the entry and proliferation of microorganisms, including bacteria, fungi, parasites, and viruses. These diseases occur when microbial interactions lead to host tissue damage, resulting in various clinical symptoms and signs. This study aimed to formulate nanoparticles of ethanol extract from matoa leaves and compare the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) values, as well as evaluate the antibacterial activity of both the extract and its nanoparticles against Cutibacterium acnes. This research was conducted experimentally. The independent variables were the concentrations of matoa leaf extract (6.25%, 12.5%, 25%, and 50%) and matoa leaf extract nanoparticles (0.625%, 1.25%, 2.5%, and 5%). The dependent variable was the antibacterial activity of both formulations against Escherichia coli and Cutibacterium acnes. Nanoparticle size characterization was performed using a Particle Size Analyzer (PSA), yielding an average size of 528.95 nm. The MIC values for C. acnes were 12.5% for the extract and 1.25% for the nanoparticles, while the MBC values were 50% and 5%, respectively. The highest antibacterial activity of matoa leaf ethanol extract against C. acnes was observed at a concentration of 50% (inhibition zone: 27.86 mm), whereas the nanoparticles exhibited a maximum inhibition zone of 26.53 mm at a 5% concentration. These findings indicate that matoa leaf extract nanoparticles exhibit strong antibacterial activity against C. acnes at lower concentrations compared to the crude extract, suggesting their potential as an effective antibacterial agent.